CLINICAL AND FUNCTIONAL EFFECTS OF MICROCURRENT NEUROSTIMULATION IN THE SYSTEM OF EARLY REHABILITATION OF CHILDREN WITH CONGENITAL MICROCEPHALY - Mambetkarimova M.S; Alimova J.B. (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Relevance. Congenital microcephaly is classified as a severe organic disorder of the central nervous system and is accompanied by persistent impairments in motor, cognitive, and speech development, as well as a high prevalence of epileptic syndromes. Conventional treatment and rehabilitation methods do not always provide sufficient functional compensation, which determines the need to introduce new non-pharmacological technologies aimed at activating neuroplasticity and regulating the functional state of the brain.